National Security Issues of the USSR
XIII, 308 p.
Keywords: LORD CARRINGTON Secretary General, North Atla/ltic Treaty Orga/lisation In providing a foreword to this volume, I have to declare an interest. I was, and am still, an enthusiastic advocate of the idea of having a resident Sovietologist at NATO headquarters, Indeed, I wondered how the work of the organisation had been done for so long without the benefit of a resident expert on a subject of such crucial interest. I was therefore delighted when an American academic of high reputation, Murray Feshbach, joined us as our first Sovietologist. I was also encouraged that he decided to organise last November a Workshop in which NATO staff could take part and which would attract prestigious participants from all the countries of this alliance, I saw for myself the high level of interest created by the Workshop, and judge it to have a very considerable success, I hope there will be other similar events in the future, There is no doubt that, in the light of the series of developments and changes launched over recent months by Mr.